Age-adjusted Charlson comorbidity index in recurrent glioblastoma: a new prognostic factor? - Barz, Melanie; Bette, Stefanie; Janssen, Insa; Aftahy, A. Kaywan; Huber, Thomas; Liesche-Starnecker, Friederike; Ryang, Yu-Mi; Wiestler, Benedikt; Combs, Stephanie; Meyer, Bernhard; Gempt, Jens (BMC neurology, 2022)
For recurrent glioblastoma (GB) patients, several therapy options have been established over the last years such as more aggressive surgery, re-irradiation or chemotherapy. Age and the Karnofsky Performance Status Scale (KPSS) are used to make decisions for these patients as these are established as prognostic factors in the initial diagnosis of GB. This study’s aim was to evaluate preoperative patient comorbidities by using the age-adjusted Charlson Comorbidity Index (ACCI) as a prognostic factor for recurrent GB patients.
Gesehen am 31.01.2023